Judicial Consideration Of Decision No. 273/Pdt.G/2021/Pa.Bkt In The Perspectives Of Benefit And Justice In Murabahah Contract - Nurjannah Septyanun; Bambang Setiaji; Rina Rohayu Harun; Indra Jaya (Universitas Muhammadiyah Surakarta, 2022)
ABSTRACT Purpose of the Study: This paper aims to analyze the judicial consideration of judges in Decision No. 273/Pdt.g/2021/PA.Bkt from the perspective of benefit and justice for all parties in the murabahah and its legal consequences. Methodology: This research used the literature review method. It used the descriptive qualitative analysis, which was conducted by profoundly reading the decision, analyzing the case, examining the appropriateness of the legal basis, and how to define them. Results: The legal considerations of judges in Decision No. 273/Pdt.g/2021/PA.Bkt are: (1) the resolution of disputes on sharia economy is the absolute authority of the Religious Court; (2) the judge assembly must maintain the legal interests and rights of the plaintiff from the actions of the defendant to undergo an auction, as well as avoiding the losses and harm that may befall the plaintiff; (3) there was an emphasis on good intentions, benefit, and justice for all parties but the judges punished the defendant to undergo rescheduling, restructuring, and reconditioning. Applications of this study: It can inspire judges to create legal reasoning that supports the aspect of legal certainty. It can inspire banks and customers to emphasize the aspects of good intention, benefit, and justice in implementing contracts. Novelty/ Originality of this study: It explained the legal consideration of judges that emphasized the aspect of mediation through contract renegotiation based on the positive law and relevant sharia principles. Keywords: Judicial consideration, murabahah contracts, banks, good intention, benefit, justice. ABSTRAK Tujuan: Tulisan ini bertujuan untuk menganalisis pertimbangan yuridis hakim dalam Putusan No. 273/Pdt.g/2021/PA.Bkt dari perspektif kemanfaatan dan keadilan bagi semua pihak dalam murabahah dan akibat hukumnya. Metodologi: Penelitian ini menggunakan metode literature review. Analisis yang digunakan adalah deskriptif kualitatif, yang dilakukan dengan membaca putusan secara mendalam, menganalisis kasus, memeriksa kesesuaian dasar hukum, dan bagaimana mendefinisikannya. Hasil: Pertimbangan hukum hakim dalam Putusan Nomor 273/Pdt.g/2021/PA.Bkt adalah: (1) penyelesaian sengketa ekonomi syariah merupakan kewenangan mutlak Peradilan Agama; (2) majelis hakim harus menjaga kepentingan hukum dan hak penggugat dari tindakan tergugat untuk menjalani lelang, serta menghindari kerugian dan kerugian yang mungkin menimpa penggugat; (3) ada penekanan pada itikad baik, kemanfaatan, dan keadilan bagi semua pihak tetapi hakim menghukum terdakwa dengan penjadwalan ulang, penataan ulang, dan rekondisi. Aplikasi penelitian ini: Dapat menginspirasi hakim untuk menciptakan penalaran hukum yang mendukung aspek kepastian hukum. Hal tersebut dapat menggugah bank dan nasabah untuk mengedepankan aspek itikad baik, manfaat, dan keadilan dalam pelaksanaan kontrak. Kebaruan/Orisinalitas: Dijelaskan pertimbangan hukum hakim yang menekankan aspek mediasi melalui renegosiasi kontrak berdasarkan hukum positif dan prinsip syariah yang relevan. Kata kunci: akad murabahah, bank, itikad baik, kemanfaatan, keadilan